Advances in Laser Hardening: A Review on Techniques, Trends and it’s Applications - Nitin Shewale; Siddhesh Takne; Prathamesh Navase; Suraj Dusane; Sachin Kakade (International Journal of Solid State Innovations & Research, 2025)
This review paper examines laser hardening, an advanced surface treatment method, and its impact on automotive components. By analyzing findings from numerous studies, the paper categorizes various laser hardening techniques and evaluates the effect of parameters like speed of scanning , power of laser and beam diameter on material performance. Special attention is given to the microstructural changes and wear resistance enhancements achieved through laser hardening, highlighting its precision and minimal thermal distortion. The review explores recent innovations, including hybrid techniques and advanced monitoring systems, aimed at improving process efficiency and addressing technical challenges. These developments underscore the potential of laser hardening as a transformative technology in surface engineering. This study provides a comprehensive understanding of current trends, future directions, and the role of laser hardening in enhancing automotive component performance.
Keywords: Laser hardening; Nd: YAG laser; Process parameters; automotive components; industrial applications; surface treatment; wear resistance